ANÁLISE DA ILUMINAÇÃO NATURAL NO AMBIENTE INTERNO A PARTIR DA ALOCAÇÃO DE JANELA PARA A DENOMINADA "ÁREA PRINCIPAL" - Bolssoni, Gabriela; Laranja, Andréa; Alvarez, Cristina (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The aim of this research was to analyze the performance of daylighting in the internal 20 ° 19'10 "S; LONG 40 ° 20'16"). The Simulations were performed with the software Troplux, for sky 7 (partly cloudy) - North orientation - and sky 3 (overcast) - all orientations, at specific points of the internal environment, for pre-established hours and days of the year. As conclusion, it was verified that only for the sky 7 (partially cloudy) - north orientation, on the months where the solar height is low (May, June and July), the daylighting losses and gains were significant, so verified that the model with the largest "main area" presented the best performance, and the illuminances did not vary proportionally with the increase of the "main area".